Стрижонок скрип: рассказы / В. П. Астафьев - Астафьев Виктор Петрович (Книга за книгой, 2016)
Экземпляры: ф.15 (20161021) / Инвентарный номер: 53635 / Цена: / Сис.шифр: Р2 / Авт.знак: А 91 / ББК: 84(2Роc=Рус)6-44